En face enhanced depth imaging optical coherence tomography of polypoidal choroidal vasculopathy. Issue 8 (5th November 2015) - Semoun, Oudy; Coscas, Florence; Coscas, Gabriel; Lalloum, Franck; Srour, Mayer; Souied, Eric H
Abstract : Purpose: To analyse retinal and choroidal changes associated with polypoidal choroidal vasculopathy (PCV) using en face spectral-domain optical coherence tomography (SD-OCT). Methods: In this retrospective and descriptive study, we collected imaging of patients affected with PCV examined using enhanced depth imaging (EDI) SD-OCT, fluorescein and indocyanine green angiography for a qualitative analysis. The three-dimensional reconstruction of 197 transverse sections with EDI SD-OCT at 30 μm intervals provided a virtual macular brick through which 496 sections in the coronal plane resulted in a C-scan or en face OCT image. Results: 30 eyes of 30 patients affected with PCV were studied. En face OCT revealed polyps as roundish structures visible deeper than pigment epithelium layer, attached to its posterior face, easily detected in all cases. Hyper-reflective dots were visible on en face OCT in all cases within the retinal layers, associated to a well-defined dark area suggesting serous exudation in 27 eyes. The abnormal choroidal network was identified in four eyes. At the Bruch membrane level, all polyps were associated with a localised back shadowing, and were no more visible at the choriocapillaris layer level. Large choroidal vessels were visible in all eyes, mainly at the polypoidal lesion periphery, not directly behind. Conclusions: En face OCT imaging using SD-OCT is an easy, reproducible, non-invasive and effective tool to visualise and to understand retinal and choroidal changes PCV. It provides complementary morphological information, describes new semiological entities and might substitute other exams in the future, without dye injection.